2010
DOI: 10.1016/j.euromechflu.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the near-field impact of an oyster table on the flow

Abstract: International audienceOyster farming structures are artificial obstacles which disturb tidal flow and wave propagation. These effects can induce modifications of erosion and sedimentation patterns, turbidity changes, local silting up and can be threatening for the shellfish farming itself. The understanding of the impact of these structures in terms of hydrodynamics and sediment dynamics in the far-field, i.e. at the scale of a bay, is a very challenging task. In order to investigate the far-field impact, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
3
18
0
1
Order By: Relevance
“…This ecosystem is thus submitted to drastic changes in terms of current fields and mud accumulation in oyster-farming habitats (Ropert & Dauvin 2000, Kervella et al 2010. These sediments display a patchy an isotropic structure of mud.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This ecosystem is thus submitted to drastic changes in terms of current fields and mud accumulation in oyster-farming habitats (Ropert & Dauvin 2000, Kervella et al 2010. These sediments display a patchy an isotropic structure of mud.…”
Section: Resultsmentioning
confidence: 99%
“…3), the resulting spatial rearrangement of soft sediments is a factor determining the colonisation by benthic diatoms in intertidal systems. Oyster farming creates physical structures that contain different physical and chemical properties than surrounding sediments (Kervella et al 2010). The spatial patterns of silt content directly reflect mechanisms that are inevitably associated with an increase of organic matter that stimulates mineralisation processes and nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coefficients of variation ranged between 5-20 %. In order to facilitate comparisons between Aber Benoît and Rivière d'Auray, the same scale was used for each study area circulation due to rearing structures has usually been reported to explain the enhanced sedimentation beneath cultures (Kervella et al 2010). In Aber Benoît, this phenomenon, associated with a relatively high density of oysters (39 tonnes per hectare), may have increased the sedimentation of fine particles beneath oysters in spite of the high current velocities generally occurring in this estuary (around 0.8-1.3 m s -1 ).…”
Section: Impact Of Oyster Culture On Grain Size and Organic Matter Pamentioning
confidence: 99%
“…Ce choix permet de considérer une immersion au réel de 4 m (valeur intermédiaire sur des estrans où elle peut varier entre 0 et 10 m), tout en conservant un nombre de configurations d'essais conséquent, la veine présentant une section d'essais de 4 m de large, 2 m de haut sur une longueur utile de 18 m. La structure ainsi réalisée (assemblage galvanisé de fer à béton de 8 mm de diamètre) présente une section de 0,5 m de large par 0,35 m de haut, pour une longueur finie de 7,2 m. Cette longueur ne permet pas de représenter une longueur de table réelle, mais est suffisante pour simuler les phénomènes en présence (KERVELLA et al, 2010) …”
Section: Approche Expérimentaleunclassified